A 19th Century American Source on Abkhazia - Nikoleishvili, Otar (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
Among the notable individuals who explored Georgia during the 19th century, it is imperative to highlight the American ethnographer, folklorist, and translator, Jeremiah Curtin. From 1864 to 1869, he served as a secretary at the US Embassy in St. Petersburg, during which time he embarked on his journey to the Caucasus. Upon his return to the United States, J. Curtin frequently delivered lectures on Russia and the Caucasus. His final visit to the Russian Empire occurred in 1900. J. Curtin’s memoirs were meticulously prepared for publication by his widow, Alma Cardell, based on his notes as an American diplomat and writer. The book was initially published in America in 1940 by the Wisconsin State Historical Society. Within these memoirs, the author narrates various accounts of his endeavors and recounts his impressions of his trip to Georgia. Notably, J. Curtin captivatingly describes numerous regions and cities of the country. This specific work exclusively focuses on episodes involving Abkhazia and the Abkhazian people. Its value is heightened by the author’s firsthand experience, as he traveled to the region in the early 1870s. In conclusion, it is fair to assert that despite some inaccuracies, Jeremiah Curtin’s memoirs must be regarded as a multifaceted and significant foreign source for studying the history of Abkhazia and Georgia as a whole.